Integrating Psychological Assessment and Legal Compliance: A Regulatory-Based Rehabilitation Framework for Children with Intellectual and Developmental Disabilities in Indonesia - Rosnalisa Zein; Iwan Kusnawirawan; Hernayati; Muhammad Arsyad Subu; Dwi Ratna Sari Handayani; Imam Waluyo (Indonesian Scientific Publication, 2026)
Children with Intellectual and Developmental Disabilities (IDD) in Indonesia face a persistent disconnect between psychological assessment, rehabilitation planning, and the realization of their legal rights. This study addresses this gap by developing and piloting an integrated pathway designed to unify these fragmented elements. We propose the Regulatory-Based Rehabilitation Framework (RBRF), a novel, structured pathway that consolidates standardized psychological assessment, individualized rehabilitation planning, and legal compliance checkpoints. Its key innovation lies in embedding legal accountability directly into the clinical rehabilitation process, an approach not previously tested in the Indonesian IDD context. A sequential mixed-methods design was employed, involving framework development informed by retrospective data, followed by a pilot implementation to evaluate feasibility, acceptability, and preliminary outcomes. Pilot results indicate that the RBRF is both feasible and well-received by families and providers. It was associated with improved coherence between assessment results, rehabilitation plans, and documented legal obligations. While modest positive trends were observed in child developmental functioning and caregiver-reported quality of life, these findings are preliminary due to the small sample size and non-controlled design. The RBRF demonstrates promise as a system-oriented approach to strengthening service coordination and accountability. This study contributes a contextually grounded model for operationalizing disability rights within rehabilitation systems, providing a foundation for future controlled trials and policy discussions in low- and middle-income settings.